Relationship Between 17-α Hydroxyprogesterone Caproate Concentration and Spontaneous Preterm Birth. Issue 3 (September 2015) - Caritis, S.N.; Venkataramanan, R.; Thom, E.; Harper, M.; Klebanoff, M.A.; Sorokin, Y.; Thorp, J.M.; Varner, M.W.; Wapner, R.J.; Iams, J.D.; Carpenter, M.W.; Grobman, W.A.; et al.
<x xml:space="preserve">Abstract</x> (Am J Obstet Gynecol. 2014;210:128.e1–128.e6)